1999
DOI: 10.1126/science.284.5413.507
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin Derivatives That Inhibit Peptidoglycan Biosynthesis Without Binding d -Ala- d -Ala

Abstract: Vancomycin is an important drug for the treatment of Gram-positive bacterial infections. Resistance to vancomycin has begun to appear, posing a serious public health threat. Vancomycin analogs containing modified carbohydrates are very active against resistant microorganisms. Results presented here show that these carbohydrate derivatives operate by a different mechanism than vancomycin; moreover, peptide binding is not required for activity. It is proposed that carbohydrate-modified vancomycin compounds are e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
252
1
6

Year Published

1999
1999
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 334 publications
(265 citation statements)
references
References 30 publications
6
252
1
6
Order By: Relevance
“…Compounds 2a-d were purified using reversed-phase HPLC according to modified literature procedure 13 and characterized by high field 1 H NMR spectroscopy and mass spectrometry (MS). The attachment of the ligands to the C-terminal of Van 4 ] 10+ , the activity of the mixture of 2d and Zn-(OAc) 2 (4:1, at pH ) 7) against VRE is the same as that of 2d, suggesting that there is no multivalent Van formed by metal complexation when 2d and Zn(OAc) 2 react at the condition of the in vitro experiment. We also did not observe the formation of [Zn(2d) n ] (2n+2)+ (n ) 1-4) by ESI-MS, which is consistent with the observed activity.…”
Section: Resultsmentioning
confidence: 91%
“…Compounds 2a-d were purified using reversed-phase HPLC according to modified literature procedure 13 and characterized by high field 1 H NMR spectroscopy and mass spectrometry (MS). The attachment of the ligands to the C-terminal of Van 4 ] 10+ , the activity of the mixture of 2d and Zn-(OAc) 2 (4:1, at pH ) 7) against VRE is the same as that of 2d, suggesting that there is no multivalent Van formed by metal complexation when 2d and Zn(OAc) 2 react at the condition of the in vitro experiment. We also did not observe the formation of [Zn(2d) n ] (2n+2)+ (n ) 1-4) by ESI-MS, which is consistent with the observed activity.…”
Section: Resultsmentioning
confidence: 91%
“…aureus cells were grown in 300 ml of defined media (20) containing [1][2][3][4][5][6][7][8][9][10][11][12][13] C]glycine and L-[ε -15 N]lysine. The cells were harvested at OD 660 = 1.0 and were complexed with 6.7 mg (4.0 μmoles) of FPBV, resulting in 66% cell-wall binding-site occupancy (15).…”
Section: Growth Of Cells and Formation Of Complexesmentioning
confidence: 99%
“…6). The second theory holds that 2 has a second mechanism of action that is independent of peptide binding (7).…”
mentioning
confidence: 99%
“…We proposed the second theory after discovering that analogues of 2 in which the peptide-binding pocket is damaged (5) still have activity against resistant microorganisms (7). These analogues were shown to inhibit the transglycosylation step of peptidoglycan biosynthesis, and we thus suggested that 2 and 5 interact directly with a component of the transglycosylation complex.…”
mentioning
confidence: 99%